Investigating language teachers’ willingness to conduct research and publish in academic journals - K. Iitula, Leena; P. S. Hamakali, Hafeni (IJRDO - Journal of Social Science and Humanities Research, 2017)
Research plays a significant role in shaping language instruction. Teachers, one of the stakeholders in education, are the closest to the data-rich field of information, the schools and particularly the classroom. This study investigates factors influencing the language teachers’ motivation to conduct research and publish in academic journals. A questionnaire was administered to 35 language teachers from secondary schools in Oshana Region. Both qualitative and quantitative data were collected and analysed using graphs and themes, respectively. The results illustrate that there are a number of factors that influence the level of teachers’ motivation to conduct research and publish their scholarly works. The findings of this study could inform teacher training institutions, educational planners or advisory teachers to integrate research and publication in their teacher training programmes and in service training programmes.